Feast-demonstration in front of the government building on Lenin square, in commemoration of the 15th anniversary of the Belorussian Socialist Soviet Republic - Popov, ...,
Feast-demonstration in front of the government building on Lenin square, in commemoration of the 15th anniversary of the Belorussian Socialist Soviet Republic.